The Role Of Foreign Ownership In Moderating The Effect Of Company Size On Intellectual Capital Disclosure - Ming Chen (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2019)
The purpose of the empirical study is to examine whether foreign ownership in moderating the relationship between company size and disclosure of intellectual capital. In this study, the variables of foreign ownership are measured by the amount of foreign ownership divided by the total number of shareholders in the company. The size of the company is proxied by Market Capitalization. Moreover, the disclosure of intellectual capital is measured by the ICD (Intellectual Capital Disclosure) Index which amounts to 25 items. The sample of this research is manufacturing companies listed on the Indonesia Stock Exchange from 2014 to 2017. This study uses the MRA model and uses SPSS as a testing tool. The result of this study is the foreign ownership is able to moderate the relationship between company size and disclosure of intellectual capital.